STUDI JUMLAH ANAK YANG DIINGINKAN DALAM PERSPEKTIF MAKRO SOSIO-EKONOMI DI INDONESIA - Sisilia Nurteta (Jurnal Kependudukan Indonesia, 2019)
Having a lot of children requires costs for fulfilling clothes, food, health, education and entertainment needs. Nowadays, families put more consideration at the value of children in terms of quality, not just quantity. The value of children is related to the number of children desired that mainly influenced by micro-level factors in the household. Nevertheless, there are indications that macro socio-economic factors also influence the number of desired fertility. This study uses correlation analysis to see the relationship between the average number of wanted children and macro variables such as contraceptive use, human development index (HDI), income per capita, proportion of poor population, age of first marriage, expenditure per capita per year, and woman’s work participation. The results show that the variables of contraceptive use, HDI, percentage of poor people, expenditure per capita, and female labour participation rate are statistically proven to affect the average number of desired children, while the variable income per capita and age at first marriage are not statistically significant. This study argued that the number of desired children is not only influenced by household micro variables but also socio-economic macro variables.